Mahabah According to KH Hasyim Asy'ari and Its Actualization on Religious Tolerance - Ryan Arief Rahman Arief Rahman; Muhammad Faishal Hibban; Burhan Lukman Syah; Bayu Sunarya (LP2M Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
This study examines the concept of mahabah in the context of Indonesian cultural and religious diversity and its potential for promoting religious tolerance. The Indonesian nation is diverse, with multiple cultures and religions, which can be a great strength or source of conflict. The worst impact of conflicts between cultures and religions is the loss of tolerance between them. To promote interfaith tolerance in Indonesia, it is important to imply the concept of mahabah in socializing, which is interpreted as love/affection in every religion. Kiai Haji Hasyim Asy'ari is an Indonesian Muslim figure who has influenced the unity of the Indonesian nation, and this study explores his concept of mahabah and its actualization on religious tolerance. The library research method collects data by studying various literature, such as books, archives, and written works related to KH Hasyim Asy'ari. According to KH Hasyim Asy'ari, mahabah, in the context of Sufism, is the faith of a servant in his god by following the Quran and Sunnah. In the social context, the servant of God will give rise to tolerance, even between religious people. By exploring the concept of mahabah in the context of Indonesian cultural and religious diversity, this study seeks to promote religious tolerance and social harmony in Indonesia.